Embedding Literacy in Indigenous Education Through Assisant Teachers: Lessons from the National Accelerated Literacy Program - Cooper, James (The Australian Journal of Indigenous Education, 2008)
Abstract This paper addresses the potential importance of assistant teachers in confronting the challenges of Indigenous literacy education. A discussion is raised with reference to a range of relevant literature, while reflections drawn from the author's involvement in evaluating the National Accelerated Literacy Program (NALP) in the Northern Territory are used to highlight an urgent need and vital opportunity to support assistant teachers – as mainstay figures in Indigenous education – in becoming “wellsprings” of literate practice and principled pedagogy. An overview of Accelerated Literacy methodology and the NALP is provided as a framework for considering how to embed strong literate practices and principled pedagogy in remote Indigenous communities through the provision of empowering professional development to Indigenous assistant teachers: facilitating for them a genuine and qualified status as literacy educators. The prospects and challenges of pursuing such an opportunity, in the context of NALP, are likewise considered.